Automated Portfolio Management and Risk Assessment System - Deshpande Kashmira Arvind, Sanjeev Thakur (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Managing an investment portfolio is no easy task, especially when markets keep changingdirection every few weeks. For a long time, this work was done by hand, with portfoliomanagers spending hours looking at charts, balance sheets, and economic reports before making any decision